Patients' use of a home-based virtual reality system to provide rehabilitation of the upper limb following stroke - Standen, Penny; Threapleton, Kate; Connell, Louise Anne; Richardson, Andy; Brown, David J.; Battersby, Steven; Sutton, Catherine Jane; Platts, F. (Oxford Academic, 2015)
Objective